PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Sinurat, Indriyani Ningsih; Daat, Sylvia Christina; Hutadjulu, Linda Y. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to examine the influence of good corporate governance and intellectual capital toÂ financial performance (financial performance). Corporate governance mechanisms in this researchÂ are managerial ownership, institutional ownership, and the proportion of independent commissioners. Intellectual capital is measured using Value Added Intellectual Capital (VAIC) modelÂ which has three components (physical capital, human capital and structural capital), and financialÂ performance is measured by return on assets (ROA). Secondary data was used by derived from theÂ financial statements of manufacturing companies listed on the Indonesia Stock Exchange 2014-2016.Â The sampling technique used purposive sampling method with multiple linear regression analysisÂ tools. Prior the regression test, the classical assumption test is done first. The results show thatÂ managerial ownership, institutional ownership and independent commissioner's proportion have noÂ effect on financial performance, while intellectual capital has an effect on financial performance. TheÂ conclusion of this research is that intellectual capital can be used to improve financial performanceÂ if company can measure accurately but corporate governance still not proven can improve company'sÂ financial performance.